If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + -9 = -5 Reorder the terms: -9 + 2a = -5 Solving -9 + 2a = -5 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 2a = -5 + 9 Combine like terms: -9 + 9 = 0 0 + 2a = -5 + 9 2a = -5 + 9 Combine like terms: -5 + 9 = 4 2a = 4 Divide each side by '2'. a = 2 Simplifying a = 2
| 2(x+8)=6x-4 | | 4x+2.14x=3.49x | | 10m+6n-2m+9n= | | 2x^2+10x=9 | | 7+4x=7x+7 | | -8(2b+3)+(17b-9)=0 | | 6x^2-66x+36=0 | | 2d+11e+9d+7e= | | 3X^7+6X^6-9X^5+6X^4= | | axb=-15 | | 9b+7b= | | ab=-15 | | 2x+3(x-5)=4x+18 | | 6x-10=2x+8 | | 4x^2+20x-48=0 | | 7a-a-a= | | 6y-2=10 | | d+e+e+d+d+e+d= | | 5x-1=4x | | 10x-6=94 | | (5a+14b-9c-8)(6)= | | 6x+2=44 | | 3x^2-10x-5=3x(1-x) | | 42x^2-14x-56=0 | | .125(2b-5)=5-b | | (3d+5)+(d-2)= | | 66-3x=24x+24 | | 3x+187=12x-11 | | 9-9x=36-30x | | 3m-(-m)= | | 2x^2+3=5x | | -8=25z+4 |